Estetika Komoditas pada Opera Batak Si Mardan - Ilham Rifandi; Susandro Susandro; Ikhsan Satria Irianto (Faculty of Languages and Arts, Universitas Negeri Padang, 2023)
Globalization affects every line of human cultural life, including theatre arts. As an important subsystem in culture, art is a manifestation of the complexity of human culture which is embedded coherently in its cultural identity. The city of Medan is a city with relatively dynamic theater development which has various groups with various theater genres. This tendency also gives rise to a tendency to use traditional culture as the basic material for creating theatrical works, for example, the Bandar Peran group. This group staged the work